Labour Law or Employment Law – a Voice in the Debate - Włodarczyk, Mirosław (Acta Universitatis Lodziensis. Folia Iuridica, 2025)
For more than two decades, there has been a debate in labour law doctrine on the need for the legitimacy of “employment law” as a new field of law. The current labour law would either be replaced by employment law or become part of it. The author call in to question the rationality of singling out the postulated construction, pointing to the risks that such a process might entail. Instead, he proposes to intensify the process of equipping persons providing work outside the employment relationship with the rights enjoyed by employees.